Engineering an aligned endothelial monolayer on a topologically modified nanofibrous platform with a micropatterned structure produced by femtosecond laser ablation. Issue 2 (9th December 2016) - Shin, Young Min; Shin, Hyeok Jun; Heo, Yunhoe; Jun, Indong; Chung, Yong-Woo; Kim, Kyeongsoo; Lim, Youn Mook; Jeon, Hojeong; Shin, Heungsoo
Abstract : Laser ablated nanofibers with micropattern regulated adhesion and orientation of HUVEC and also contributed to generate an aligned endothelial monolayer. Abstract : A monolayer of endothelial cells (ECs) aligned along the direction of blood flow plays crucial roles in the regulation of anti-thrombogenic and pro-inflammatory reactions in the blood vessel wall. Thus, many researchers have attempted to mimic the aligned structure of ECs in vascular grafts or tissue-engineered blood vessels. In the present study, we fabricated micro-groove patterned nanofibers using a femtosecond laser ablation technique to recapitulate the densely organized anisotropic architecture of the endothelial layer. Femtosecond laser ablation enabled us to generate high-resolution groove patterns (10 μm width) with 20 or 80 μm gaps on randomly oriented electrospun nanofibers. The patterned nanofibers exhibited anisotropic (transverse: 101.1 ± 4.0° and longitudinal: 123.5 ± 9.4°) water contact angles; however, the mechanical properties were consistent in both directions. The micropatterned nanofibers modulated the aligned structure or aspect ratio (20 μm: 0.23 ± 0.11 and 80 μm: 0.42 ± 0.18) of ECs along the pattern direction. In particular, the engineered aligned endothelial layer was effective in eliciting an anti-inflammatory response (approximately 50% greater than that of random or aligned nanofibers), thereby effectively preventing monocyte adhesion following activation by TNF-α treatment. Therefore, micropatterning by laser ablation can be utilized to generate high-resolution microgrooves on various substrates, thereby providing fundamental platforms for vascular tissue engineering.